Pengaruh Harga, Promosi, Dan Desain Produk Terhadap Pembelian Sepeda Motor Yamaha (Studi Kasus Area di Sekitar Universitas Muhammadiyah Surakarta) - Agantha, Moh. ferry; , Drs. Sujadi, MM (2016)
In this study aims to determine the individual (partial) the effect of pricing, promotion, and product design to the purchase of a Yamaha motorcycle (A case study in the area around the University of Muhammadiyah Surakarta).The population in this study is that consumers consumers who ever bought and put on a Yamaha motorcycle. The sampling method using purposive sampling method selected sample of a population by using specific criteria or considerations. The criteria / sampling in this research is that consumers who use Yamaha motorcycle in the area around the University of Muhammadiyah Surakarta. To facilitate the research and the limitations of the study period, the total sample of 100 respondents. The analytical method used in this research is by using multiple linear regression analysis and hypothesis testing by t-test, and the coefficient of determination.Based on the results of multiple linear regression analysis can be concluded the following research: Results of t test (partial) that individually (partial) price significantly influence purchasing decisions Yamaha motorcycles, individually (partial) sale significantly influence purchasing decisions Yamaha motorcycles, and individually (partial) product design significantly influence purchasing decisions Yamaha motorcycle.